General physiology of oligodendrocytes and Schwann cells - Butt, Arthur M. (Henry Stewart Talks, 2011)
Demyelination, Schwann cells, SC in PNS injuries and demyelination, CNS dysmyelination in the absence of laminin or neuregulin signaling, The myelin sheath, Node of Ranvier, Role of gap junctions and potassium channels, Myelin proteins, Oligodendrocytes
Archived at 2022/07/31